Seroprevalence of hepatitis A virus in a cross-sectional study in Mexico: Implications for hepatitis A vaccination - Lazcano-Ponce, Eduardo; Conde-Gonzalez, Carlos; Rojas, Rosalba; DeAntonio, Rodrigo; Romano-Mazzotti, Luis; Cervantes, Yolanda; Ortega-Barria, Eduardo (Human vaccines & immunotherapeutics, 2013)
Hepatitis A virus (HAV) remains a public health concern worldwide contributing to significant morbidity in developed and developing countries. This cross-sectional database study estimated the overall HAV seroprevalence and the seroprevalence by gender, age, region and socioeconomic status in Mexico. Between January and October 2010, serum samples collected during the National Health and Nutrition survey (ENSANUT 2006) were obtained from subjects aged 1-95 y. Subjects' gender, age, geographical region and socioeconomic status were extracted from the survey and compiled into a subset database by the Mexican National Institute of Public Health. Anti-HAV antibodies were measured using a chemiluminescent immunoassay. A total of 3658 subjects were included in the according-to-protocol cohort. Overall, the HAV seroprevalence was 84.2%. The HAV seroprevalence rates were similar between females (86.1%) and males (82.2%). The percentage of subjects seropositive for anti-HAV antibodies was highest in adults aged ≥ 20 y (96.9%), followed by adolescents aged 10-19 y (80.1%) and lowest in children aged 1-9 y (45.0%) (p < 0.0001). Regionally, the highest HAV seroprevalence rate was observed in the South (88.8%) followed by Central and Northern Mexico and Mexico City (p = 0.02). The HAV seroprevalence was similar between subjects of high socioeconomic (90.1%) status and of low socioeconomic status (86.6%). This study confirms the intermediate HAV endemicity in Mexico. Cost-effectiveness studies are necessary to evaluate the inclusion of an effective hepatitis A vaccine from a population-based perspective in addition to continuous efforts to improve hygiene and sanitation that have a substantial impact on the disease burden.